Size recognition of external molecules on polymer brushes using aggregation-induced emission - Sim, Xuan Ming (2023)
Aggregation-induced emission (AIE)-driven fluorescent polymer brushes, i.e., poly(4-(1,2,2-triphenylvinyl)phenyl methacrylate) (PTPMA) brushes, were fabricated in a patterned manner with different graft-density domains. The obtained patterned brushes served as a molecular size analyzer; namely, the sizes of external molecules were recognized via the changes in the fluorescence intensities of the polymer brushes. Small-size external molecules were able to enter the polymer brush layers, inducing the fluorescent side groups in the brush chains to aggregate and enhancing the fluorescence intensity via AIE. On the other hand, large-size external molecules were unable to enter the polymer brush layer, resulting in no significant change in the fluorescence intensity. The size exclusion (molecular weight) threshold of external molecules depends on the graft density. As a demonstration, the present work distinguished external molecules with molecular weights of 300 and 1000 via the change in the fluorescence intensity of the brushes with different graft densities. The present patterning technique can tune the graft density in a wide range and hence may offer patterned brushes with a wide range of analyzable molecular sizes.